Respuesta :
Answer:
= [tex]x^2 + 3x - 10[/tex]
Step-by-step explanation:
in factored form, find the equation where plugging x in will result in 0
plugging -5 or 2 into (x + 5)(x - 2) will result in 0
to change this from factored to standard form, FOIL
when you FOIL, (a + b)(c + d) = ac + ad + bc + bd
(x +5)(x - 2)
= (x * x) + (x * -2) + (5 * x) + (5 * -2)
= [tex]x^2 -2x + 5x - 10[/tex]
= [tex]x^2 + 3x - 10[/tex]
Answer:
[tex](x + 5)(x - 2) \\ x(x - 2) + 5(x - 2) \\ {x}^{2} - 2x + 5x - 10 \\ = {x}^{2} + 3x - 10[/tex]